The role of waterfalls in the structure of macroinvertebrate communities of the Tevenek River (Lake Teletskoye basin, Northeastern Altai) - Yanygina, Liubov V.; Shipunov, Petr A. (Acta Biologica Sibirica, 2022)
Extreme waterfall conditions cause partition of aquatic ecosystems of waterfall streams into discrete zones. To assess the features of aquatic ecosystems that function in waterfall streams, macroinvertebrate communities of the Tevenek River (Lake Teletskoye basin, Northeastern Altai) were examined above and below the waterfall. The diversity, abundance, and biomass of macroinvertebrates were higher above than below the barriers. Gammarus korbuensis showed the most significant decrease in number (from 3.1 to 2.3 thousand ind./m2) probably due to the intensive use of amphipods as food for fish living in Lake Teletskoye. An additional factor in favor of the high species richness of macroinvertebrates in the upper reaches is the geomorphology of the waterfall river valley that contributes to the formation of more diverse conditions above the waterfalls. Hydrobiological studies of waterfall streams can help to understand the restructuring of benthic communities divided as a result of the human impact.